Need of Alertness on Porcine Circovirus 2 in North East India - Rajesh JB; Rajkhowa S; Dimri U; Prasad H; Sarma K; Behera SK (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
The domestic pig originated from the Eurasian wild boar (Sus scrofa) and its domestication started approximately 9,000 years ago [1]. Asian pig domestication appeared to have occurred mainly in North-eastern India, the Mekong region, and the middle and downstream regions of the Yangtze River [2]. The pig population in India is 8.8 million, which is 1.09% of the world's pig population of 967.38 million [3].